Evidence to Improve Physical Activity among Medically Underserved Older adults: A Scoping Review. (16th April 2018) - Hu, Yi-Ling; Junge, Kristin; Nguyen, An; Hiegel, Kelsey; Somerville, Emily; Keglovits, Marian; Stark, Susan
Abstract: Background and Objectives: Participation in leisure physical activity (PA) and engagement in PA interventions among older adults is influenced by socioeconomic status (SES), race/ethnicity, and environment. However, studies of PA for medically underserved older adults have not yet been systematically evaluated. The objective of this study is to map the nature and extent of research conducted on PA participation, interventions, and components of effective leisure PA programs for medically underserved older adults. Research Design and Methods: The five-stage approach was used to conduct this scoping review. We searched PubMed, CINAHL, and Cochrane Library for peer-reviewed studies published between 2006 and 2016. Data extracted from selected studies included study population, study type, purpose of intent, evidence level, barriers to PA participation, and components of PA intervention. Results: Three hundred and ninety-two articles were identified, and 60 studies were included in the final data charting. Existing literature showed that most studies remained descriptive in nature, and few intervention studies have achieved a high level of evidence. Among 21 intervention studies, only 4 were explicitly conducted for older adults. Culturally adapted materials, race/ethnicity-specific barriers and facilitators, and form of intervention were important components for intervention programs. Discussion and Implications: Findings indicate that more studies are needed to reduce health disparities related to PA participation for medically underserved older adults. Intervention components such as race/ethnicity-relevant barriers and facilitators and culturally sensitive materials are also needed for PA interventions targeting underserved older adults in order to provide evidence for best practices.